Highly advanced scientific titles in the field of reading pedagogy - Soler, Marta Viviana (2014)
The immediate need of non-English speaking advanced university students, young fellows and young researchers to read literature in English urges the teaching of selective reading of a variety of academic and highly-advanced scientific texts within the framework of English as a foreign language, particularly English for Specific and Academic Purposes. The aim of this work is to analyze one possible operationalization of an expeditious reading strategy through the reading of highly advanced scientific titles of research papers in terms of cause-effect relationships, as this is as important and necessary as reading abstracts for fast tracking relevant data. Because of the scarce literature available on this topic, our analysis is prudently restricted to a small set of title samples. Still, the strength of our observations lie in that scientific titles demonstrate to be very useful authentic sample material in the field of reading pedagogy, this being an issue neither fully explored nor exploited to date.